Iron in Drinking Water and its Impact on Human Health –A Study in Selected Units of Jalalabad Cantonment - Rahman, Irtika; Wahab, Md Abdul; Akter, Monowara; Mahanta, Timir Ranjan (Bangladesh Armed Forces Medical Journal, 2024)
Background: Prevalence of diseases due to appearance of excessive amount of iron in drinking water is increasing day by day. Often people are unaware about the harmful effects of excess iron that may be present in drinking water. Sometimes they overlook minor symptoms. Adequate study was not conducted before to rule out actual scenario. The aim of this study is to represent the detrimental effect of excessive iron in drinking water as well as to create awareness to get rid of it. Methods: A cross-sectional study was carried out in 17 units of 17 Infantry Division, Jalalabad Cantonment, Sylhet covering the period of January 2019 to May 2019. Total 52 participants were selected purposively who had been suffering from various kinds of abdominal symptoms; their source of drinking water was marked. Water was collected from 5 different sources to see iron level. Again they were monitored after establishing Reverse Osmosis water filter. Iron level at drinking water was also tested each time at laboratory by Atomic Absorption spectrometry method. Informed written consent was taken from the patients. A semi-structured questionnaire was developed and data were collected by face to face interview. Analysis was done by using Statistical Package for the Social Sciences (SPSS version 25). Results: Among 52 respondents, maximum i.e. 25(48.07%) developed moderate to severe constipation followed by 16(30.76%) developed dyspepsia and while others i.e.11(21.15%) had both the symptoms. Symptoms were most severe among the persons who used to drink water having highest concentration of Iron (1.9 mg/L). After establishment of Reverse Osmosis water purifier the iron concentration in water reduced significantly and only 4(8%) had constipation and 6(12%) had dyspepsia. Conclusion: Iron is a natural constituent of drinking water. But considering the harmful impact of excessive iron present in drinking water to human health, regular monitoring should be ensured to identify the risk group. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 58-64